2014
DOI: 10.1186/1471-2407-14-616
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1246 enhances migration and invasion through CADM1 in hepatocellular carcinoma

Abstract: BackgroundThe aberrant expression of microRNAs has been demonstrated to play a crucial role in the initiation and progression of hepatocarcinoma. miR-1246 expression in High invasive ability cell line than significantly higher than that in low invasive ability cell line.MethodsTranswell chambers (8-uM pore size; Costar) were used in the in vitro migration and invison anssay. Dual luciferase reporter gene construct and Dual luciferase reporter assay to identify the target of miR-1246. CADM1 expression was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 28 publications
4
73
0
Order By: Relevance
“…This is not surprising, given that miRNAs are known to target multiple targets. For instance, and as mentioned above, miR‐1246 has also been reported to enhance aggressive cancer phenotype by targeting the tumor suppressor, CADM1 . We speculate that there may be other mRNAs/pathways that miR‐1246 targets to regulate cancer stemness in HCC.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This is not surprising, given that miRNAs are known to target multiple targets. For instance, and as mentioned above, miR‐1246 has also been reported to enhance aggressive cancer phenotype by targeting the tumor suppressor, CADM1 . We speculate that there may be other mRNAs/pathways that miR‐1246 targets to regulate cancer stemness in HCC.…”
Section: Discussionsupporting
confidence: 52%
“…miR‐1246 have also been found to promote angiogenesis by activating small mothers of decapentaplegic 1/5/8 signaling elicited by promyelocytic leukemia down‐regulation in endothelial cells . In HCC, miR‐1246 has been shown to enhance metastasis by targeting cell adhesion molecule 1 (CADM1), a tumor‐suppressor gene involved in cell‐cell interactions . Circulating miR‐1246 has also been recently shown to predict tumor recurrence and survival in HCC patients after liver transplantation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, this study also demonstrated that miR-1246 induced secretion of key pro-inflammatory cytokines and chemokines (IL-6, CCL2 and CCL5) in MSCs was mediated via NF-κB signaling pathway [25]. At the functional level, miR-1246 had been shown to induce the proliferation, invasion and migration and enhance cell apoptosis of cervical or hepatocellular carcinoma cells [28, 29]. In our study, we found that our results were consistent with previous studies, that overexpression of miR-1246 strengthened the decrease in cell viability, the increase in apoptosis, and the overproduction of pro-inflammatory factors after LPS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-1246 was an oncogenic miRNA linking with cancer migration and invasion [46], but there was no literature concerning the role of miR-1246 in radiosensitivity. Figure 3 shows that inhibition of miR-1246 in A549 cells bearing a high level of intrinsic miR-1246 significantly suppressed cell proliferation and increased cell radiosensitivity; while transfection of H446 cells with miR-1246 mimic promoted cell growth and enhanced cell radioresistance.…”
Section: Discussionmentioning
confidence: 99%